Sporolithon sp1 structural integrity responses across the PETM - Leanne Melbourne; Daniela N Schmidt; Suman Sarkar (PANGAEA, 2025)
This dataset contains cell measurements (length, width and wall thickness) for an unidentified coralline alga of the genus Sporolithon, labelled Sporolithon sp1. Samples were extracted from limestone collected in 2015 and 2020 in Meghalaya, NE India (Eastern Tethys), corresponding to a time before and during the Palaeocene-Eocene Thermal Maximum, PETM (~55.8 Ma).
In: Melbourne, L et al. (2025): Assessing structural integrity responses of coralline algae across the PETM [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.978487